Identificação de Helicobacter sp. na mucosa gástrica de sagüis (Callithrix sp.), com avaliação de alterações histopatológicas e de diferentes métodos de diagnóstico - Mello, Marcela Freire Vallim de (2005)
Gastric microflora from humans and animals has been intensely studied since the discovery of the Helicobacter genus and its association with gastrointestinal diseases. Old World nonhuman primates have been proposed as experimental animal models for investigation of these pathogens. Nevertheless, few reports about Helicobacter infection in New World Primates and no studies on Brazilian nonhuman primates are available. The objectives of this study were to investigate the presence of Helicobacter sp. and to describe the pathologic findings in the gastric mucosa of captive marmosets (Callithrix sp.). Thirty adult males and females marmosets, being six Callithrix jacchus, twelve C. kuhli, and twelve C. geoffroyi, were studied. Histologic specimens from fundic, corpus, and antral gastric regions were collected from neutral-buffered 10% formalin-fixed stomachs. Specimens were routinely processed in paraffin for light microscopy. Sections were stained with hematoxylin-eosin (HE) and the Warthin-Starry (WS) silver impregnation method, and immunostained with rabbit anti-H. pylori polyclonal antibody, anti-type I and anti-type III collagen polyclonal antibodies and anti-type IV collagen monoclonal antibody. Immunohistochemistry (IHC) tests were used as standard examination for the Helicobacter sp. infection diagnosis. Fifteen stomachs had positive results in the IHC tests, while Helicobacter-like organisms (HLOs) were present in silver-stained sections from 29 stomachs. Inflammatory mononuclear cell infiltrates with predominance of lymphocytes among plasma cells and macrophages, in the lamina propria of gastric mucosa, and lymphoid follicles were the most common histopathological findings observed in Helicobacter sp.-positive and negative marmosets. Collagens type I, III and IV were detected in Helicobacter sp.-positive and negative marmosets gastric wall, with no obvious differences between the two groups relative to intensity or sites of collagens expression. Immunohistochemistry was thought to be efficient in detecting Helicobacter sp. in marmosets. The silver staining technique demonstrates bacillary and coccoid forms without identifying the genus of the bacteria, ultimately leading to false positive results. In this study, marmosets were found to be susceptible to Helicobacter sp. natural-occurring infection, and to present gastric lesions, thereby opening the way to the development of comparative studies on Helicobacter sp. infection in humans